Trauma-informed approach for bridging ethnic distance in post-conflict societies - Kuhar, Metka (Metodološki zvezki, 2023)
The article presents a pilot study based on intervention conducted in Croatia in 2022. De-spite intensive peacebuilding efforts, ethnic tensions in post-conflict societies remain high,suggesting that current strategies may be missing critical components. This experimentintegrated recent neurophysiological findings, particularly polyvagal theory, into peace-building intervention. The intervention involved a two-day seminar in Zagreb, wheretrauma-informed, body-based techniques were used to address post-war trauma. Partici-pants learnt to recognise and manage trauma reactions by promoting their interoceptiveawareness and a felt sense of safety. The seminar included both theoretical and experientialcomponents, focusing on the impact of trauma on the autonomous nervous system andinterpersonal dynamics. The study used an experimental design with intervention andcontrol group to investigate the effects of the seminar. Measures included interoceptiveawareness, autonomic reactivity, ethnic distance, perspective taking and mental well-being.The results showed that the participants in the intervention group showed significantimprovements in interoceptive awareness, particularly in not worrying and emotionalawareness subscales compared to the control group. However, ethnic distance scores didnot decrease as expected, highlighting the complexity of changing deep-rooted attitudes.The study faced some challenges, including participant recruitment and the short durationof the intervention, which may have limited its effectiveness. Despite these limitations, thefindings suggest that integrating trauma-informed approaches into peacebuilding effortsholds promise for improving interethnic relations. Future research should focus on longerinterventions and diverse participant groups to better understand the potential of thesemethods in various contexts.
Keywords: ethnic distance; etnična distanca; Etnični odnosi; gradnja miru; interoceptive awareness; interoceptivno zavedanje; peacebuilding; polivagalna teorija; polyvagal theory; post-conflict societies; postkonfliktne družbe; Psihične travme; trauma; trauma-informed peacebuilding; travma